2013
DOI: 10.1002/lary.24045
|View full text |Cite
|
Sign up to set email alerts
|

Change of obstruction level during drug‐induced sleep endoscopy according to sedation depth in obstructive sleep apnea

Abstract: The degree of upper airway narrowing can be aggravated according to the sedation depth. The monitoring of sedation depth during DISE is critical, especially in patients with mouth breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 24 publications
0
39
0
1
Order By: Relevance
“…Eighteen snorers, 30 mild (AHI: 5-15), 30 moderate (AHI: [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and 30 severe (AHI: > 30) OSA patients were enrolled in this study. Sixty-six patients with OSA (73.3%) were male.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen snorers, 30 mild (AHI: 5-15), 30 moderate (AHI: [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and 30 severe (AHI: > 30) OSA patients were enrolled in this study. Sixty-six patients with OSA (73.3%) were male.…”
Section: Resultsmentioning
confidence: 99%
“…Even when using propofol TCI, the BIS values, while performing DISE, were found to vary from 44 to 98. 24 Hong et al 16 recently demonstrated that the upper airway narrowed with deeper sedation according to BIS level (above 70 versus below 70) in a small number of cases. The current study set a narrower sedative range to yield greater reproducibility.…”
Section: A B C D E F G H Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prior investigations have examined the relationship of BIS during sedation and natural sleep, as well as the effects of sedation on airway obstruction, the results have not been consistent. [5][6][7][8] While BIS levels decrease during natural sleep in much the same way as during sedation, the technology does not allow for discrimination of different stages of sleep.…”
mentioning
confidence: 99%
“…Although prior investigations have examined the relationship of BIS during sedation and natural sleep, as well as the effects of sedation on airway obstruction, the results have not been consistent. [5][6][7][8] While BIS levels decrease during natural sleep in much the same way as during sedation, the technology does not allow for discrimination of different stages of sleep. 9 Furthermore, BIS scores associated with depth of anesthesia are dependent upon the anesthetic agent being used, are relatively ineffective during sedation with ketamine, nitrous oxide, or dexmedetomidine, and can be unpredictable in the presence of opioids.…”
mentioning
confidence: 99%